2019
DOI: 10.3390/min9070387
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Parameters for the Dissolution of Mn from Manganese Nodules with the Use of Tailings in An Acid Medium

Abstract: Manganese nodules are an attractive source of base metals and critical and rare elements and are required to meet a high demand of today’s industry. In previous studies, it has been shown that high concentrations of reducing agent (Fe) in the system are beneficial for the rapid extraction of manganese. However, it is necessary to optimize the operational parameters in order to maximize Mn recovery. In this study, a statistical analysis was carried out using factorial experimental design for the main parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Several studies have been carried out in recent years for the extraction of Mn from marine nodules in acidic media, testing diverse reducing agents such as oxalic acid [9], glucose [10], FeO [11], cane molasses [12], corn cob [13], biomass from residual tea [14], etc. Toro et al [15,16] obtained promising results when employing FeSO 4 , formed from the reaction between tailings and H 2 SO 4 . Benavente et al [7] conducted a study for the dissolution of Cu and Mn from black copper under oxidizing and reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out in recent years for the extraction of Mn from marine nodules in acidic media, testing diverse reducing agents such as oxalic acid [9], glucose [10], FeO [11], cane molasses [12], corn cob [13], biomass from residual tea [14], etc. Toro et al [15,16] obtained promising results when employing FeSO 4 , formed from the reaction between tailings and H 2 SO 4 . Benavente et al [7] conducted a study for the dissolution of Cu and Mn from black copper under oxidizing and reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The polymetallic nodules are rock concretions formed by concentric layers of hydroxides [20]. Their high content of base, critical and rare metals makes them commercially interesting [21][22][23]. Their metal content includes high concentrations of Co, Ni, Te, Ti, and Pt, as well rare earth elements [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The Cu extraction rates was studied through the effects of time and chloride and H 2 SO 4 concentrations variables on leaching covellite [37][38][39][40]. An experimental design was carried out considering three levels per factor, resulting in a total of 27 samples [41]. The fit of the multiple linear regression model was generated in the statistical software Minitab 18 (version 18, Pennsylvania State University, State College, PA, USA), studying the linear and quadratic effects and the interactions of the factors considered in the study [42], as shown in Equation 9.…”
Section: Experimental Designmentioning
confidence: 99%